Satellite Culture and Eliot’s Glencoe - Gish, Nancy K. (Complutense Journal of English Studies, 2014)
T. S. Eliot’s one poem about Scotland is a verbal response to landscape unparalleled in his work and significant in its recognition of what cannot be appropriated or assimilated. Although one critic, in 1975, called it Eliot’s “only great short lyric,” it has almost never been discussed or even mentioned in subsequent criticism. In its recognition, however, of a scene and history beyond what his other work reveals, “Rannoch, by Glencoe” not only represents a momentary realization of history and geography outside his own, it counters Eliot’s social analysis of cultures he defines as “satellite,” or subsidiary to his concept of “the greater peoples.” In “Notes towards the Definition of Culture,” Eliot argues that the importance of literature from “regions” combines the “stronger” culture’s connection of the satellite to the “world at large” and the “satellite” culture’s contributions to developing and enriching the “stronger.” Yet in “Rannoch, by Glencoe” Scotland and its tragic history are merged in a landscape and consciousness with power and significance in and for Scotland itself.